Accogliere senza integrare: le distorsioni delle politiche sull’immigrazione nel Mezzogiorno d’Italia - La Bella, Marco (SocietàMutamentoPolitica, 2020)
The essay focuses on the integrated System of Protection of Asylum Seekers and Refugees (SPRAR) as a key feature of immigration policies in Italy. This system, beyond the most recent constraining norms on security, currently shows experiences of excellence, as in the case of Sprar/Siproimi nets. However, the reception system as a whole present still some critical weakness on the ground of immigrants’ integration, and particularly in the South of the country, since a “complete” integration have to deal with mechanisms of job placement and the structural characteristics of the labor market.